Sistem Monitoring Suhu dan Kelembaban Berbasis IoT (Internet of Thing) pada Gudang Penyimpanan PT Sakafarma Laboratories - Santosa, Risam; Sari, Putri Anggun; Sasongko, Ananto Tri (Prodi Sistem Informasi Universitas Dharma Andalas, 2023)
Monitoring temperature and humidity using the conventional method currently used at PT Sakafarm Laboratories still faces several obstacles, such as delays in recording and lack of data accuracy. The purpose of this research is to design and implement a temperature and humidity Monitoring system based on the Internet of Things (IoT) in a raw material storage warehouse at PT Sakafarma Laboratories. This study used the prototype method with NodeMCU ESP8266, DHT11, Buzzer as the main hardware component and Thinger.Io as the user interface. The results of this study, an IoT-based temperature and humidity Monitoring system can make it easier for users to monitor temperature and humidity in real time and the resulting data is more accurate and efficient, the results of temperature and humidity testing are classified as normal and according to predetermined specifications, namely 20-30 0C and <85 RH, and sensor accuracy for temperature values ​​reached 98.49% while sensor accuracy for humidity values ​​reached 87.78%.